2018
DOI: 10.1103/physrevlett.121.235901
|View full text |Cite
|
Sign up to set email alerts
|

Variational Principle for Mass Transport

Abstract: A variation principle for mass transport in solids is derived that recasts transport coefficients as minima of local thermodynamic average quantities. The result is independent of diffusion mechanism, and applies to amorphous and crystalline systems. This unifies different computational approaches for diffusion, and provides a framework for the creation of new approximation methods with error estimation. It gives a different physical interpretation of the Green function. Finally, the variational principle quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Eqs. (26), (27) and (28) are the group G's infinitesimal generating functions, ε σ are independent infinitesimal parameters related to ω.…”
Section: Iiunifying Investigations For Canonical Variational Principmentioning
confidence: 99%
See 1 more Smart Citation
“…Eqs. (26), (27) and (28) are the group G's infinitesimal generating functions, ε σ are independent infinitesimal parameters related to ω.…”
Section: Iiunifying Investigations For Canonical Variational Principmentioning
confidence: 99%
“…A lot of references, e.g., [23][24][25][26][27][28] have very well investigated various variational principles and their useful actual applications, and lots of good works, e.g., [29], [30], [31] have very well researched on Noether's Theorem and the useful pratical applications in different branches of physics.…”
Section: Iintroductionmentioning
confidence: 99%
“…Path factorization amounts to constructing the triangular matrices involved in LU or LDL T decomposition as well as their inverses, as shown in Appendix B. It is shown that the repeated application of updating rules (32) and (33) to obtain τ (N ) and θ (N ) from τ (0) and θ (0) amounts to directly applying the inverted triangular factors on τ (0) and θ (0) . Noticeably, transitions to new transient states are removed within path factorization in the same way as matrix elements are canceled through Gaussian elimination.…”
Section: K Path Factorization and Space-time Randomizationmentioning
confidence: 99%
“…They are obtained by inverting a matrix, which amounts to summing over all paths between two consecutive vacancy-solute exchanges. Green functions used in atomic transport theory [31,32] also appear as pseudo-inverses of transition rate matrices and may also be interpreted as geometric sums of path probabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation